Understanding Intestinal Microbiota in Equine Grass Sickness: Next Generation Sequencing of Faecal Bacterial DNA. (September 2015) - Leng, J.; Proudman, C.; Blow, F.; Darby, A.; Swann, J.
Abstract : Reasons for performing study: The bacteria Clostridium botulinum has been associated with equine grass sickness (EGS); however, the effect on the wider horse's gut microbiome is currently unknown. Objectives: To characterise the bacterial dysbiosis that occurs within the gut microbiome of horses with EGS and to identify and quantify Clostridium botulinum within the faecal microbiota of the affected horses. Study design: Case–control study. Methods: Faecal samples were collected from horses with a histological diagnosis of EGS and matched controls. Faecal bacterial DNA was extracted and sequenced to characterise the microbial communities in the group. Faecal samples were collected from a total of 33 horses over 2 years. This included 13 EGS cases, 14 matched controls and 6 hospital controls. Faecal bacterial DNA was extracted from samples and the v4 region of the bacterial 16S rRNA gene was amplified. DNA was sequenced on the MiSeq platform and data was analysed using QIIME. Differences in community profile between the 3 groups of horses were identified using linear discriminant analysis effect size (LEfSe) method. Results: There was a significant increase in Bacteroidetes and a decrease in Firmicutes bacteria in horses with EGS compared to the 2 control groups. Discriminant analysis identified bacterial genera Desulphovibrio and Veillonella and the bacterial species Veillonella parvula as increased in abundance. There was no noticeable increase in C. botulinum in the faecal microbiome of EGS horses in this study. Conclusions: The dysbiosis characterised by bacterial sequencing showed a similar shift to that identified previously in colitis horses and human inflammatory bowel disease. It is currently unclear how Verrucomicrobia bacteria are linked to grass sickness. Ethical animal research: The study was approved by The University of Liverpool ethics committee. Owner informed consent was obtained before sampling.Sources of funding: The Equine Grass Sickness Fund and The University of Reading.Competing interests: None declared.